Moving Beyond the Flat Tax - Tax Policy Reform in the Slovak Republic - Remeta, Ján (OECD Taxation Working Papers, 2015)
The Slovak Republic was among the fastest growing OECD economies in the last decade. It is broadly recognised that the 2004 tax reform contributed to this success. Ten years after this fundamental reform, however, the time has come to re-evaluate some of the key characteristics of the Slovak tax system. The Slovak economy faces multiple challenges including an ageing population, a persistently high unemployment rate, significant regional disparities, skills gaps and risks related to the increasing international competition for mobile capital. Can the Slovak tax system in its present form prevail against these headwinds? The paper shows that the current tax system suffers from weaknesses that constrain its capacity to raise additional revenues and to create the conditions for inclusive and sustainable economic growth. Although measures have recently been introduced to address some of these challenges, additional tax reforms and a further strengthening of the tax administration will be needed. The OECD worked jointly with the Institute for Financial Policy (IFP) of the Slovak Ministry of Finance to provide an overall assessment of the Slovak tax system and recommendations for future tax policy reforms